An experimental study on shear capacity of interfaces in recycled aggregate concrete. (15th February 2018) - Waseem, Shakeel Ahmad; Singh, Bhupinder
Abstract : Forty‐eight initially uncracked push‐off specimens were used for the investigation of the interface shear strength of natural and recycled coarse aggregate concrete. The parameters varied in the push‐off tests were the recycled aggregate replacement level (0, 50, and 100%), the clamping force across the shear‐transfer plane and the concrete grade (normal‐ and medium‐strength). The inclined cracks crossing the shear plane, noted before the development of shear cracks, were indicative of the truss like action for resisting shear in push‐off specimens. An analytical approach based on the truss modeling of the force system within the push‐off specimens using the method initially proposed by Mattock and Hawkins has been used for prediction of interface cracking stress of both the concrete types. Calibration of the proposed analytical procedure has been done with the help of the experimental results of the tested push‐off specimens. Using the experimental results as well as comparable results from the literature, a shear‐friction regression equation accounting for the effect of concrete grade, normal force on the shear plane and the recycled coarse aggregate replacement level has been proposed for shear strength.